RESPONS KRISTEN TERHADAP PERBUDAKAN: PERSPEKTIF MORAL, BIBLIKA, DAN TEOLOGI REFORMED - Roedy Silitonga (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
This article examines Kant's moral philosophy alongside Biblical and theological perspectives on modern slavery as a consequence of human sin and the fall. Using a phenomenological qualitative approach in a literature study, the author analyzes the root causes of slavery—poverty, low education levels, and weak law enforcement—and explores Christian ethical responses rooted in love and justice. The study integrates Kantian morality with Biblical teachings and Reformed theological thought to develop a holistic understanding of morality that bridges ethics and spirituality. The findings emphasize the importance of education, effective law enforcement, and support for marginalized communities as practical measures to combat slavery and human trafficking. This paper highlights the novelty of interdisciplinary dialogue between philosophy and theology in promoting human dignity and social justice.